Interactions between Epichloë endophyte and the plant microbiome impact nitrogen responses in host Achnatherum inebrians plants - Yuanyuan Jin; Zhenjiang Chen; James F. White; Kamran Malik; Chunjie Li (Microbiology Spectrum, 2024)
ABSTRACTThe clavicipitaceous fungus Epichloë gansuensis forms symbiotic associations with drunken horse grass (Achnatherum inebrians), providing biotic and abiotic stress protection to its host. However, it is unclear how E. gansuensis affects the assembly of host plant-associated bacterial communities after ammonium nitrogen (NH4+-N) treatment. We examined the shoot- and root-associated bacterial microbiota and root metabolites of A. inebrians when infected (I) or uninfected (F) with E. gansuensis endophyte. The results showed more pronounced NH4+-N-induced microbial and metabolic changes in the endophyte-infected plants compared to the endophyte-free plants. E. gansuensis significantly altered bacterial community composition and β-diversity in shoots and roots and increased bacterial α-diversity under NH4+-N treatment. The relative abundance of 117 and 157 root metabolites significantly changed with E. gansuensis infection under water and NH4+-N treatment compared to endophyte-free plants. Root bacterial community composition was significantly related to the abundance of the top 30 metabolites [variable importance in the projection (VIP) > 2 and VIP > 3] contributing to differences between I and F plants, especially alkaloids. The correlation network between root microbiome and metabolites was complex. Microorganisms in the Proteobacteria and Firmicutes phyla were significantly associated with the R00693 metabolic reaction of cysteine and methionine metabolism. Co-metabolism network analysis revealed common metabolites between host plants and microorganisms.IMPORTANCEOur results suggest that the effect of endophyte infection is sensitive to nitrogen availability. Endophyte symbiosis altered the composition of shoot and root bacterial communities, increasing bacterial diversity. There was also a change in the class and relative abundance of metabolites. We found a complex co-occurrence network between root microorganisms and metabolites, with some metabolites shared between the host plant and its microbiome. The precise ecological function of the metabolites produced in response to endophyte infection remains unknown. However, some of these compounds may facilitate plant-microbe symbiosis by increasing the uptake of beneficial soil bacteria into plant tissues. Overall, these findings advance our understanding of the interactions between the microbiome, metabolome, and endophyte symbiosis in grasses. The results provide critical insight into the mechanisms by which the plant microbiome responds to nutrient stress in the presence of fungal endophytes.